2023
DOI: 10.53660/clm-979-23c15
|View full text |Cite
|
Sign up to set email alerts
|

HLA-I allelic variants related to resistance and susceptibility to severe SARS-CoV-2 infection

Abstract: Objective: Identify allelic variants of HLA I related to possible resistance or susceptibility to severe SARS-CoV-2 infection and describe this relationship. Methods: This study is a descriptive literature review based on articles published between the years 2020 and 2021 in the databases: SciELO, ScienceDirect, PubMed /MEDLINE, Capes Periodicals, BVS, Wiley Online Library; that was available in Brazilian Portuguese and English. Results: The analyzed studies demonstrated that HLA I alleles can be considered li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This is due to the fact that these alleles have the ability to bind to SARS-CoV-2 peptides, leading to the modulation of the immune response against the virus. 40 Several studies have employed a similar approach to design peptides for the protein S of SARS-CoV-2. Baruah et al found five CD8+ T cell epitopes YLQPRTFLL, GVYFASTEK, EPVLKGVKL, VVNQNAQAL, and WTA-GAAAYY, along with eight B cell epitopes that are more likely to bind MHC class I commonly found in China.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that these alleles have the ability to bind to SARS-CoV-2 peptides, leading to the modulation of the immune response against the virus. 40 Several studies have employed a similar approach to design peptides for the protein S of SARS-CoV-2. Baruah et al found five CD8+ T cell epitopes YLQPRTFLL, GVYFASTEK, EPVLKGVKL, VVNQNAQAL, and WTA-GAAAYY, along with eight B cell epitopes that are more likely to bind MHC class I commonly found in China.…”
Section: Discussionmentioning
confidence: 99%